(untitled) - Evans, John. (San Francisco, Calif.,Oxford, 2007)
QoS, short for "quality of service," is one of the most important goals a network designer or administrator will have. Ensuring that the network runs at optimal precision with data remaining accurate, traveling fast, and to the correct user are the main objectives of QoS. The various media that fly across the network including voice, video, and data have different idiosyncrasies that try the dimensions of the network. This malleable network architecture poses an always moving potential problem for the network professional.
Keywords: Computer networks,Computer networks,MPLS standard,Multicasting (Computer networks),Mạng máy tính,Tiêu chuẩn MPLS; Quality control,Reliability,Kiểm soát chất lượng